Conspectus of Patagonian fossil penguins. American Museum novitates - Simpson, George Gaylord, 1902-; Ameghino, Florentino, 1853-1911. (New York, N.Y. : American Museum of Natural History, 1972)
37 p. : ill. 24 cm. Includes bibliographical references (p. 35-37). "The known fossil penguins of Argentina are all from the Patagonia Formation, mostly from its basal part, in Chubut and Santa Cruz, probably early Miocene but possibly late Oligocene in age. They are here reviewed on the basis of collections in the American Museum of Natural History, the Museo Argentino de Ciencias Naturales, the Museo de La Plata, and the British Museum (Natural History), and of publications mostly by Florentino Ameghino. Four genera are accepted as valid: Palaeospheniscus Moreno and Mercerat, with four accepted species, Chubutodyptes Simpson, with one accepted species, Paraptenodytes Ameghino with three accepted species (one, P. brodkorbi, here new, of dubious reference to this genus), and Arthrodytes Ameghino, with one accepted species. Numerous other names proposed by Ameghino are reduced to synonymy. Palaeospheniscus, the most abundant genus, covers a considerable range in size, and its separable size groups are here considered species. The correct name for the largest size group, hitherto called P. robustus, is P. wimani, as the holotype of robustus belongs in Paraptenodytes. Neculus may be a valid spheniscid genus, but it is virtually undefinable at present. Palaeoapterodytes was based on an error and is unidentifiable. Cruschedula, Cladornis, and Argyrodyptes were not penguins. The average size of the Patagonian fossil penguins is decidedly smaller than the average for their mostly older known relatives from New Zealand, Australia, and Seymour Island, only Arthrodytes grandis being distinctly larger than the living emperor penguin. No Patagonian genus is surely known from any other region. The Patagonian fossil penguin fauna is richer than any other known, fossil or Recent, but it is possible that not all the species were strictly synchronous and sympatric"--P. [1].